PENGARUH MINAT MEMBACA SISWA TERHADAP PRESTASI BELAJAR BAHASA INDONESIA SISWA KELAS III MIN 3 PURWOREJO - indah sundari; Saifudin Zuhri (As-Sibyan, 2021)
This research is field research that looks at the problems of reading interest on learning Bahasa Indonesia in grades III at MIN 3 Purworejo with the problems and how students reading interes, how is the achievement of Indonesian students in grade III and is there an effect of reading interest on Indonesian learning achievement achieved by students grade III at MIN 3 Purworejo. Therefore, the writer raised the title “The Influence of reading interest on Indonesian learning achievement of grade III students of MIN 3 Purworejo”. This type of research is quantitative research using inferential statistical techniques, namely statistical techniques, namely statistical techniques used to analyze sample data and the results aplly to the population. Research location at MIN 3 Purworejo. Furthermore, the population in this study were all grade III students at MIN 3 Purworejo. Data collection techniques were collected through questionnaires, interviews, and documentation which were then analyzed through parametric statistical statistics with a simple Linear regression formula. Based on the results of research and statistical analysis carried out using a simple linear regression formula, the results of the calculation of Pearson’s Product Moment correlation indicate that the statue = 0,828 > ttabel = 0,297 with a significant level of 5% means that reading interest has a strong relationship with Indonesia learning achievement. The result of the ttest calculation shows that thitung = 9,802 > tabal = 2,000 with a significance level of 5%. The result of the calculation of the test Fcount = 96,070 and Ftabel =2,2 with a significant level of 5% the result of the coefficient (R2) = 0.686 whitch show that reading interest affects the Indonesian language learning achievement by 68% while the other 32% is influenced by other factors.